Precise and efficient pose estimation of stacked objects for mobile manipulation in industrial robotics challenges. (3rd July 2019) - Lim, Gi Hyun; Lau, Nuno; Pedrosa, Eurico; Amaral, Filipe; Pereira, Artur; Luís Azevedo, José; Cunha, Bernardo
Abstract : Object manipulation tasks such as picking up, carrying and placing should be executed based on the information of objects which are provided by the perception system. A precise and efficient pose estimation system has been developed to address the requirements and to achieve the objectives for autonomous packaging, specifically picking up of stacked non-rigid objects. For fine pose estimation, a drawing pin shaped kernel and pinhole filtering methods are used on the roughly estimated pose of objects. The system has been applied in a realistic industrial environment as a challenging scenario for the Challenge 2 – Shop Floor Logistics and Manipulation on a mobile manipulator in the context of the European Robotics Challenges (EuRoC) project. GRAPHICAL ABSTRACT: